Super-cognition in aging: Cognitive profiles and associated lifestyle factors. Issue 6 (1st November 2020) - Yu, Junhong; Collinson, Simon L.; Liew, Tau Ming; Ng, Tze-Pin; Mahendran, Rathi; Kua, Ee-Heok; Feng, Lei
Abstract: Previous research on older adults with superior cognitive abilities (super-cognition) has typically examined cognition using a single domain approach, which may not adequately capture the multidimensional nature of successful cognitive aging. Furthermore, the lifestyle factors associated with super-cognition have not been studied adequately. The current study examined the cognitive profiles and lifestyle factors associated with super-cognition. Community-dwelling older adults ( N = 693) were administered neuropsychological tests and self-reported measures of lifestyle factors at midlife (retrospectively recalled). Then, using an a priori set of criteria, we classified them as super-cognition or normal. A latent class analysis was conducted to examine the different cognitive profiles of super-cognition, and both groups were compared on their lifestyle-related outcomes. A total of 64 and 263 participants met the criteria for super-cognition and normal participants respectively. A three-class solution best described super-cognition among our participants. Approximately half of them had superior immediate memory; two other smaller groups of participants with super-cognition had superior attention, language, and visuospatial abilities. Participants with super-cognition reported less participation in social activities and, frequently, working more than 9 hours/day and feeling stressed, at midlife. Super-cognition among the elderly is associated with having a busier, more socially-isolated and stressful midlife.